Side skin reactions of multikinase inhibitors in treatment of thyroid cancer - F. S. Sevryukov; E. V. Borodavina; Р. А. Isaev; V. V. Polkin; А. А. Ilyin; S. V. Vasilkov; Yu. А. Panaseykin; D. N. Derbugov; S. А. Ivanov; S. О. Podvyaznikov; А. D. Kaprin (Опухоли головы и шеи)
Dermal toxicity of anti-cancer drugs apparent in patients with thyroid cancer. This side effect appears, in particular, in relation to increased administration of targeted anti-cancer treatment, especially tyrosinkinase inhibitors, towards various receptors of growth factors which are applied in the ethiopathogenesis of a tumor cell. Our article focuses on the dermatotoxity, designated also as skin reaction, which most frequently occurs in patients treated by tyrosinkinase inhibitors – sorafenib, vandetonib, cabozantinib and lenvantinib. High prevalence of dermatotoxity, reported by patients, treated with these drugs underscores the need for greater understanding of the pathogenesis and management of this syndrome.